Environmental drivers of the vital urban coastal zones: An explorative case study based on the data-driven multi-method approach - Yin, Yuting; Shao, Yuhan; Lu, Huilin; Han, Yun (Frontiers in Ecology and Evolution, 2022)
Success in delivering dynamic urban coastal zones is considered essential, as it brings enormous opportunities to the social, economic, ecological and cultural development of the cities in addition to benefitting the coastal zones. However, the environmental drivers contributing to urban coastal zone vitality remain uncertain due to unclarified spatial boundaries and the influences of diverse characteristics from surrounding contexts. This study aims at exploring environmental drivers that can vitalize urban coastal zones and can inform an effective way to instruct design procedures. It sets out from clarifying the spatial boundaries of urban coastal zones and emphasizing the mutual connections among its spatial components. A data-driven multi-method approach is used to analyze spatial forms, traffic organizations, land uses, landscape characteristics and coastal functions of the eight typical coastal cases selected in different countries. Results suggested that six typical coastal zone types can be classified based on landscape characteristics and coastal functions, while the other vitality-related aspects, spatial forms, traffic organizations and land uses, are analyzed to imply design requirements for each type. It is found that requirements on vitality-related aspects of the six types evidently vary with the coastal functions, but there are similarities among the types with similar landscape characteristics.